EFFECTIVENESS OF GROUP COUNSELING USING THE MIND MAPPING TECHNIQUE TO IMPROVE CAREER PLANNING AMONG 12TH_GRADE STUDENTS AT SMA TUNAS KELAPA SAMARINDA FOR THE 2024/2025 ACADEMIC YEAR - Zidan Rais , Rifqi; Sari Pratiwi, Yasintha; Syarifudin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Abstract This research is based on issues related to students' career planning. According to the results of a need assessment using AUM, 37.5% of students face problems regarding careers and employment, a relatively high percentage at SMA Tunas Kelapa Samarinda, indicating that students have not yet been able to effectively plan their careers. The study was conducted from August 19 to 30, 2024, with the aim of determining the effectiveness of the mind mapping technique in improving the career planning of 12th-grade students at SMA Tunas Kelapa Samarinda for the 2024/2025 academic year. This is an experimental study using a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 6 students, selected using purposive sampling. Data collection was carried out using a questionnaire. The data analysis technique employed in this study was parametric statistics, specifically the paired t-test. The results of the study showed an improvement in students' career planning, with an average pretest score of 117.8 and an average posttest score of 134. The t-test analysis produced a sig. (2-tailed) value of 0.005, which is less than 0.05, indicating a significant difference between the pretest and posttest scores. In line with the research question, the results demonstrate that the mind mapping technique is effective in improving students' career planning. Thus, it can be concluded that this study aligns with the research question and the author's hypothesis. The conclusion of this study is that the career planning of 12th-grade students at SMA Tunas Kelapa Samarinda for the 2024/2025 academic year can be improved through group counseling services using the mind mapping technique.